Quo Vadis Revisi UU Penyiaran - Yusanto, Yoki; Sjuchro, Dian Wardiana; Amdan, Nana Sutisna; Ramadhan, Aditya; -, Muhaemin (representamen, 2024)
Law of the Republic of Indonesia Number 32 Year 2002 on Broadcasting was born after the political struggle in Indonesia. It gave birth to the Indonesian Broadcasting Commission (KPI) to equalize the ownership of radio and television, thus creating a diversity of content. But now KPI's authority is weaker after the House of Representatives passed the UU Cipta Kerja. KPI's role is only like an NGO. Now the Broadcasting Law will be revised by the House of Representatives. The Program is in the form of broadcast content, who supervises it, what is the role of KPI after the Undang-undang Cipta Kerja. Instead of being an independent institution, KPI now seems to be a broadcasting Non-Governmental Organization (NGO). This research uses a qualitative method. The research was conducted by interviewing KPI commissioners in various regions in Indonesia. The authority of the Indonesian Broadcasting Commission (KPI) as an independent body must remain firm and robust, standing as the leading regulator for broadcasting institutions, both radio and television, as well as for digital media content. For social justice in Indonesia, media ownership diversity must be regulated in the revised Broadcasting Law. Ensuring media ownership diversity across various regions and sectors is essential to prevent media ownership monopolies, which could result in only a few entities controlling television and radio broadcasting.